The level of knowledge and attitude related to HIV/AIDS among health science students - Roslee Rajikan; You, Yee Xing; Amirah Aqilah Abd Rahim; Nurin Iman Ahmad Kamal; Noor Syaffiera Mohd Sharif; Tan, Yen Yee; Amirah Abdul Halim; Dalila Abdul Talib; Muhammad Azif Azizi Md Noh (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2017)
HIV/AIDS is a worrying health issues among Malaysian young adult. This is probably due to the level of knowledge and attitude related to the disease. This cross-sectional study was conducted to determine the level of knowledge and attitude related to HIV/AIDS among health science students in a Malaysian public university. A total of 216 students were involved in this research (male and female). Respondents were recruited using stratified random sampling. Both level of knowledge and attitude related to HIV/AIDS was assessed by using HIV Knowledge Questionnaires (HIV-KQ). The questionnaires consisted of three parts. The first part was about sociodemographic, second part knowledge related to HIV/AIDS and the last part was about the attitude related to HIV/ AIDS. Most of the respondents were Malays (67%), followed by Chinese (26%), Indians (5%) and others (2%). The results found that the level of knowledge about HIV/AIDS among 1st year and 2nd year health science students were low. The average of HIV/AIDS knowledge scores of all respondents were 9.41±2.876. Their main source of information for HIV/AIDS came from internet, newspaper and television. Majority of the respondents showed more openness and positive attitudes towards HIV/AIDS. In conclusion, although the level of knowledge about HIV/AIDS among health science students in a malaysian public university is low, they showed positive attitudes towards HIV/AIDS. Thus more internet based and youth-friendly education program are required.